Non-alcoholic fatty liver disease is not a causal risk factor for psoriasis: A Mendelian randomization study of 108,835 individuals - Näslund-Koch, Charlotte; Bojesen, Stig Egil; Gluud, Lise Lotte; Skov, Lone; Vedel-Krogh, Signe (Frontiers in Immunology, 2022)
Background: Psoriasis is observationally associated with a higher risk of non-alcoholic fatty liver disease (NAFLD); however, the causal relationship between the two diseases remains unclear. Objective: We hypothesized that individuals with NAFLD or elevated liver fat content have higher risk of psoriasis and that NAFLD is a causal risk factor for psoriasis. We tested this using a Mendelian randomization approach. Methods: We included 108,835 individuals from the Danish general population, including 1,277 individuals with psoriasis and 802 individuals with NAFLD according to ICD codes. To estimate liver fat content, a subset of the participants (N = 7,416) also had a CT scan performed. First, we tested whether a diagnosis of NAFLD or elevated liver fat content was observationally associated with risk of psoriasis. Subsequently, we used the genetic variants PNPLA3 and TM6SF2, both strongly associated with NAFLD and high liver fat content, to test whether NAFLD was causally associated with increased risk of psoriasis. Results: Observationally, individuals with vs. without a diagnosis of NAFLD had higher risk of psoriasis with an odds ratio of 2.03 (95% confidence interval 1.28-3.21). The risk of psoriasis increased in a stepwise manner with increasing liver fat content with an odds ratio of 5.00 (2.63-9.46) in individuals in the highest quartile of liver fat content compared to individuals in the lowest quartile. In genetic analyses, PNPLA3 and TM6SF2 were both associated with increased risk of NAFLD but not with increased risk of psoriasis. Conclusion: Observationally, a diagnosis of NAFLD or elevated liver fat content was associated with higher risk of psoriasis. However, using genetic variants as a proxy for NAFLD, we did not find evidence of a causal relationship between NAFLD and psoriasis. Thus, the observational association between NAFLD and psoriasis is presumably a result of shared confounding factors or reverse causation.